Targeted proteomics reveals strain‐specific changes in the mouse insulin and central metabolic pathways after a sustained high‐fat diet - Eduard Sabidó; Yibo Wu; Lucia Bautista; Thomas Porstmann; Ching‐Yun Chang; Olga Vitek; Markus Stoffel; Ruedi Aebersold (Molecular Systems Biology)
Abstract The metabolic syndrome is a collection of risk factors including obesity, insulin resistance and hepatic steatosis, which occur together and increase the risk of diseases such as diabetes, cardiovascular disease and cancer. In spite of intense research, the complex etiology of insulin resistance and its association with the accumulation of triacylglycerides in the liver and with hepatic steatosis remains not completely understood. Here, we performed quantitative measurements of 144 proteins involved in the insulin‐signaling pathway and central metabolism in liver homogenates of two genetically well‐defined mouse strains C57BL/6J and 129Sv that were subjected to a sustained high‐fat diet. We used targeted mass spectrometry by selected reaction monitoring (SRM) to generate accurate and reproducible quantitation of the targeted proteins across 36 different samples (12 conditions and 3 biological replicates), generating one of the largest quantitative targeted proteomics data sets in mammalian tissues. Our results revealed rapid response to high‐fat diet that diverged early in the feeding regimen, and evidenced a response to high‐fat diet dominated by the activation of peroxisomal β‐oxidation in C57BL/6J and by lipogenesis in 129Sv mice.